POLA DISTRIBUSI DAN MARGIN PEMASARAN GABAH DI KABUPATEN KARAWANG - Nurul Aeunnisa; Djoko Sumarjono (Universitas Wahid Hasyim, 2018)
The purpose of this research is to analyze the difference of government floor price of grain with the average costs of paddy, analyzing the distribution pattern of grain amd amalyze marketing margins of grain in Karawang Region. The benefit from this research is to design and efficient the grain distribution in Karawang Region and this study can be used as reference for practitioners and stakeholder in taking policy on grain price. Methods used in this study is survey. The location chosen by purposive. The amount of respondent were 82 respondents using the snowball method. The analysis using descriptive and statistics One sample t-test, the calculation of the avarage cost of paddy, the percentage of patterns and the calculation of the margin marketing. The results showed that there are differences of grain price of avarage cost by IDR. 3.531 and the price of grain non government by an average of IDR. 4.347 with the floor price of the government (HPP) commodity the grain by IDR. 3.700 in significantly. There are two patterns of marketing grain which is a long pattern there are farmers – broker – ricemill with the percentage of 67 %, and the short pattern there are farmers – ricemill with the percentage of 33 %. The margin value of long pattern by IDR. 250 per kilogram, while the short pattern IDR. 0 per kilogram. There are differences, the long pattern with the short pattern in significant. Keywords: Farming, operational cost paddy, pattern, margin.